Problem-Based Learning with Science, Technology, Engineering, and Mathematics (Stem) Approach to Improve Critical Thinking Skills and Conceptual Understanding of Junior High School Students - Rr. Arum Setyorini; Anna Permanasari; Didit Ardianto (JSEP (Journal of Science Education and Practice), 2021)
This research has done to examine the application of learning with PBL STEM model implemented in one of State Junior High School in Bogor. The method used in this research was quasi experiment with pre-post control design. The experimental class was treated with PBL STEM model, while the control class with PBL model 5M. The subjects involved were 76 students of Junior High School in one of Bogor City, divided into 38 students in experimental class 38 students in control class. Data collection techniques conducted in this study through observation, tests, and questionnaires. Data analysis was performed using quantitative data analysis and qualitative data analysis. The research shows the increasing of student’s critical thinking skill high category (N-Gain value is 70.78%). The Implementation of PBL STEM could improve the concept gaining with the N-Gain value is as much as 69.56%. So, it can be concluded that problem-based learning with STEM approach is appropriate to be implemented in junior high school students of class VIII. In addition, students' responses showed positive results can be seen from the increased interest, liveliness, motivation, in studying the field of STEM.